Grace darling - Vicary, Tim (Nxb. Đồng Nai, 2009)
All they could hear was the wind, and the waves crashing on to the rocks. All they could see was the night. They could not see the ship, broken in two. They could not see the people holding on to the dark wet rock, slowly dying of cold. And they could not hear the cries for help - only the wind. How could they save the people on the rock? Was their wooden boat stronger than the iron ship? Were a man and his daughter stronger than the great waves that broke the ship in two? The Forfarshire was wrecked off the north-east coast of England in 1838. This is the true story of Grace Darling - a girl who became a famous heroine on that stormy night.